THE EFFECT OF JOB SATISFACTION, JOB ENVIRONMENT AND ORGANIZATIONAL COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AND ITS IMPACT ON PERFORMANCE - Praptono Soeharto; Tantri Widiastuti (Journal of Management and Business, 2015)
The purpose of this research was to analyze the effect of Job Satisfaction, JobEnvironment and Organizational Commitment on Organizational Citizenship Behavior (OCB)and its impact on Employee Performance. The population in this research were all teacherson Terang Bangsa Christian Junior High School and Senior High School Semarang totaling 103 teachers. The entire population was used as sample. The analysis technique used was Structural Equation Model (SEM) with Partial Least Square (PLS) approach. This result of this research showed that Job Satisfaction, Job Environment and Organizational Commitment had positive and significant effect on Organizational Citizenship Behavior (OCB). Job Satisfaction. Job Environment and Organizational Commitment did not effect Employee Performance. Organizational Citizenship Behavior (OCB) had positive and significant effect on Employee Performance.